Chemical profiling and dermatological and anti-aging properties of Syzygium jambos L. (Alston): evidence from molecular docking, molecular dynamics, and in vitro experiments - Mahdi, Ismail; Imbimbo, Paola; Ortaakarsu, Ahmet Buğra; Adhiambo Ochieng, Melvin; Ben Bakrim, Widad; Drissi, Badr Eddine; Ibrahim, Mohammed Auwal; Abdelfattah, Mohamed A. O.; Mahmoud, Mona F.; Monti, Daria Maria; Sobeh, Mansour (Frontiers in Molecular Biosciences, 2024)
The phytoconstituents of the aqueous extract from Syzygium jambos L. (Alston) leaves were defined using HPLC-PDA-MS/MS and the antioxidant, anti-aging, antibacterial, and anti-biofilm activities of the extract were in silico and in vitro investigated. The antioxidant activities were performed using in vitro DPPH and FRAP assays as well as H2-DCFDA assay in HaCaT cells in which oxidative stress was induced by UVA radiation. Anti-aging activity was tested in vitro, using aging-related enzymes. The antibacterial, anti-biofilm and inhibitory effects on bacterial mobilities (swarming and swimming) were assessed against Pseudomonas aeruginosa. Results showed that S. jambos aqueous extract contained 28 phytochemicals belonging to different metabolite classes, mainly phenolic acids, gallic acid derivatives, flavonoids, and ellagitannins. Mineral content analysis showed that S. jambos leaves contained moderate amounts of nitrogen, potassium, manganese, magnesium, and zinc, relatively low amounts of phosphorus and copper, and high concentration of calcium and iron. The extract displayed strong antioxidant activities in vitro and inhibited UVA-induced oxidative stress in HaCaT cells. Docking the major compounds identified in the extract into the four main protein targets involved in skin aging revealed an appreciable inhibitory potential of these compounds against tyrosinase, elastase, hyaluronidase, and collagenase enzymes. Moreover, molecular dynamic simulations were adopted to confirm the binding affinity of some selected compounds towards the target enzymes. The extract exhibited pronounced in vitro anti-aging effects, compared to kojic acid and quercetin (the reference compounds). It also inhibited the growth of P. aeruginosa, counteracted its ability to form biofilm, and impeded its swarming and swimming mobilities. Altogether, these findings strongly propose S. jambos leaves as a promising source of bioactive metabolites for the development of natural cosmeceutical and dermatological agents.